2015
DOI: 10.1136/ejhpharm-2015-000686
|View full text |Cite
|
Sign up to set email alerts
|

Medication discrepancies revealed by medication reconciliation and their potential short-term and long-term effects: a Norwegian multicentre study carried out on internal medicine wards

Abstract: PurposeTo investigate the extent of medication discrepancies (MDs) revealed by medication reconciliation (MR) and to assess the potential clinical relevance of the MDs for the patients in a short-term and long-term perspectives.MethodsPatients ≥18 years admitted to five internal medicine wards were included in this prospective study. MDs between the medication list obtained by physicians at hospital admission and medication list obtained by a structured MR process by pharmacists were identified and assessed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 15 publications
7
35
1
Order By: Relevance
“…Compared with two studies with similar profiles regarding approach, definitions and healthcare systems,8 10 discrepancies on admission were more frequent in the present study (4.1/patient vs 3.2/patient8 and 3.4/patient10). We attribute this difference to external factors.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Compared with two studies with similar profiles regarding approach, definitions and healthcare systems,8 10 discrepancies on admission were more frequent in the present study (4.1/patient vs 3.2/patient8 and 3.4/patient10). We attribute this difference to external factors.…”
Section: Discussioncontrasting
confidence: 60%
“…We attribute this difference to external factors. For example, our cohort had a high number of drugs (9.1 drugs after reconciliation vs 6.08 and 7.2)10 and frequent changes in medication. Both studies reported a positive correlation between the number of drugs on admission and the number of discrepancies observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding that the participants used in average 4.2 regular drugs is in line with other studies reporting on persons with chronic conditions using in average 3-5 regular drugs. [19][20][21] Only a third of the participants in our cohort used oral spasmolytic drugs regularly, even though nearly 80% of them reported at least some level of spasticity. The explanation could be that mild spasticity can have a positive impact on functionality, or the fact that the most common oral spasmolytic drugs come with undesirable side effects as sedation and dizziness.…”
Section: Discussionmentioning
confidence: 88%
“…1 Up to 27% of all hospital prescribing errors can be attributed to medication histories being incomplete at the time of admission, with 27% to 83% of patients having at least 1 medication history error at the time of admission with the potential to adversely affect care over the long term. [6][7][8] Accreditation Canada does not identify which patients would be considered at high risk and which would be most at risk for adverse drug events. Therefore, Canadian emergency departments must develop a risk assessment approach to identify these groups.…”
Section: 3mentioning
confidence: 99%